Education and Social Mobility For Orang Asli Papua - Alfath Bagus Panuntun El Nur Indonesia (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2021)
Papuan human resources are complicated due to educational barriers that make it difficult for indigenous Papuans (OAP) to achieve upward social mobility. Many factors have contributed to these educational barriers, including poverty, conflict and war, a lack of teachers, and poor infrastructure. These obstacles should be solved through the main feature of the Special Autonomy Law (SAL), namely the